Assessing the Effects of Artificial Intelligence on Startup Performance: An Analysis of Transformational Initiatives - Brian Domini; Andha Sari Dewi; Galih Putra Cesna (Pandawan Sejahtera Indonesia, 2023)
The research paper discusses the impact of Artificial Intelligence (AI) on organizational and process-level performance. The study follows a four-step process: analyzing AI technologies, exploring case studies, collecting data, and reviewing AI literature. The findings indicate that AI has various technologies, such as machine translation, chatbots, and self-learning algorithms, that can enhance automation, information, and transformation effects. Organizations can use AI to improve processes, optimize operations, and develop strategic and competitive advantages. The study provides insights into how organizations can enhance the business value of their transformation projects by leveraging AI's attributes. The research framework proposes a more comprehensive approach to account for the intangible benefits of AI in organizations. The study highlights that AI combines several configurations of IT in various industries, and organizations should reconfigure their processes to achieve performance through AI capabilities. The research also provides tangible evidence about the business value of AI-based projects and their impact on firm performance, considering it not as a single technology but as a set/combination of several different configurations of IT in various industries. The study has scientific and managerial interests and proposes a model for analyzing the impact of AI on firm performance, providing managers with insights to improve their organizations' performance, profitability, and competitive advantage.